Strategi Pemerintah Taiwan dalam Meningkatkan Ekspor Agrikultur melalui Economic Cooperation Framework Agreement (ECFA) - Pramesti, Azalia Ayu; Purbantina, Adiasri Putri (Jurnal Transformasi Global, 2021)
The relationship between China and Taiwan since separating in 1949 continues to fluctuate, particularly with the One China Policy. However, despite the political tension between the two, they have close bilateral economic ties relations, where China is Taiwan's largest trading partner. China and Taiwan signed an agreement entitled "Cross-Straits Economic Cooperation Framework Agreement" (ECFA) in 2010. The ECFA challenges Taiwan's agricultural sector. This paper evaluates how the Taiwanese government response to boost the competitiveness of their agricultural exports through three channels: 1) foreign policies, 2) trade regulations, and 3) supports to domestic firms. Keywords: Free Trade Agreement, Foreign Policy, Trade Regulations, Firms